Interim Dismissal of DPRD Members Who Commit Criminal Offenses - Justitia, Airlangga Justitia; ., Lufsiana; Wijoyo, Suparto; Nainggolan, Samuel Dharma Putra (Journal of Ecohumanism, 2024)
Indonesia adheres to representative democracy within it’s constitutional system. This representative democracy is manifest by a general election mechanism to elect candidates who will occupy strategic position in managing the running of government. The candidate must be affiliated with a political party in participating in the general election because according to the laws and regulations the general election participants are political parties. A candidate needs a political party to take part in the general election, thus the relationship between the candidate and the political party is like superiors and subordinates with the theme of regeneration. This relationship persistes until the candidate is elected as a member of the regional people’s representative council (DPRD). In addition, political parties hace the authority to impose inter-term termination (PAW) on their cadres who are already sitting in the regional people’s representative council (DPRD) based on the terms and conditions set out in the law. This research is a legal research that uses a statutory approach and a conseptual approach to answer the legal issues contained in this research.